Deepfakes : creation, detection, and impact - Gaur, Loveleen (Boca Raton : CRC Press, 2023)
"Apart from technological introduction to deepfakes concept, the book details algorithms to detect deepfakes, techniques for identifying manipulated content and identifying face swap, generative adversarial neural networks, media forensic techniques, deep learning architectures, forensic analysis of deepfakes and so forth"--
Introduction to deepfake technologies / Loveleen Gaur, Saurav Mallik, Noor Zaman Jhanjhi.
OCLC-licensed vendor bibliographic record.
Keywords: Deepfakes; Disinformation -- Prevention; Disinformation -- Social aspects; COMPUTERS / Computer Graphics / General; COMPUTERS / Machine Theory; TECHNOLOGY / Electricity